Efficacy and Safety of Argon Laser Peripheral Iridoplasty and Systemic Medical Therapy in Asian Patients with Acute Primary Angle Closure: A Meta-Analysis of Randomized Controlled Trials - Wenting Cai; Qiyang Lou; Jiaqi Fan; Donghui Yu; Tianyi Shen; Jing Yu (Journal of Ophthalmology)
Purpose. The purpose of this meta-analysis was to assess the percent reduction in the intraocular pressure (IOP) after argon laser peripheral iridoplasty (ALPI) and systemic medical therapy in patients with acute primary angle closure (APAC). Methods. We searched a number of electronic databases, including MEDLINE, EMBASE, PubMed, and Cochrane Library. We searched the electronic databases from the inception of the databases to August 2018. The primary outcomes included the IOP reduction (IOPR), percent reduction in IOP (IOPR%) from baseline to the endpoint and peripheral anterior synechiae (PAS). The secondary outcomes included the cup-to-disc ratio (CDR), mean endothelial count, and percent of patients requiring topical glaucoma medication. Summary weighted mean difference (WMD), odds ratio (OR), and 95% confidence intervals (CIs) were calculated. Results. Four eligible studies including 183 eyes (92 in the ALPI group and 91 in the medical therapy group) were identified. When comparing ALPI to medical therapy, the WMDs of the IOPR% were 30.03 (95% CI: 21.33 to 38.72, p<0.00001) at 15 minutes, 27.39 (95% CI: 18.89 to 35.89, p<0.00001) at 30 minutes, 18.15 (95% CI: 10.63 to 25.68, p<0.00001) at 1 hour, and 12.91 (95% CI: 4.50 to 21.32, p=0.003) at 2 hours. There was no statistically significant difference between the two groups at 24 hours and at more than 6 months after therapy. Meanwhile, no significant difference was observed in the degree of PAS, CDR, mean endothelial count, and percent of patients requiring topical glaucoma medication after treatment between the two groups. Conclusions. Both ALPI and systemic medications were effective with regard to decreasing the IOP. ALPI was more effective in lowering the IOP within the first two hours. Therefore, ALPI may be a better choice for rapidly lowering the IOP in patients with APAC within a short period.